The power motive as a predictor of receptiveness to nonverbal behavior in sport - Furley, Philip; Schweizer, Geoffrey; Wegner, Mirko (Motivation and emotion, 2019)
The study tested the hypothesis that the implicit power motive is positively associated with receptiveness to nonverbal cues related to submissiveness in sports. Participants’ (N = 156) implicit and explicit power motives were measured. Receptiveness to nonverbal dominance and submissiveness cues was measured using videos from sports competitions depicting elite athletes who are supposed to send nonverbal signals dependent on the current score. Participants’ task was estimating if athletes were currently trailing or leading. Participants’ estimates were compared to the actual score in the video scenes. Results suggest that participants scoring high in the implicit power motive were more receptive towards submissive cues, but not more receptive towards dominant cues. This finding suggests that the implicit power motive is associated with a greater receptiveness for cues related to submissiveness.